Ring-opening fluorination of bicyclic azaarenes. Issue 3 (5th January 2022) - Komatsuda, Masaaki; Suto, Ayane; Kondo, Hiroki; Takada, Hiroyuki; Kato, Kenta; Saito, Bunnai; Yamaguchi, Junichiro
Abstract : A ring-opening fluorination of bicyclic azaarenes was developed. Although this overall transformation can be classified as an electrophilic fluorination of aromatics, it is a novel type of fluorination that results in construction of tert -C–F bonds. Abstract : We have discovered a ring-opening fluorination of bicyclic azaarenes. Upon treatment of bicyclic azaarenes such as pyrazolo[1, 5- a ]pyridines with electrophilic fluorinating agents, fluorination of the aromatic ring is followed by a ring-opening reaction. Although this overall transformation can be classified as an electrophilic fluorination of an aromatic ring, it is a novel type of fluorination that results in construction of tertiary carbon–fluorine bonds. The present protocol can be applied to a range of bicyclic azaarenes, tolerating azines and a variety of functional groups. Additionally, mechanistic studies and enantioselective fluorination have been examined.